IMPLEMENTATION MECHANISM OF THE STATE POLICY TO PROVIDE ECONOMIC SECURITY OF MACHINE-BUILDING INDUSTRY - REDKVA, Oksana (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The paper has analyzed the impact of state policy on ensuring the economic security of machine-building enterprises. It has been suggested the mechanism of the state policy for ensuring economic safety of the machine-building complex of the country which is based on certain target principles. This mechanism will allow diagnosing the state of the enterprise and determining the efficiency of commodity production, which will enable to integrate the complex of measures and factors that threaten it. The priorities and top-priority goals of the state policy in the field of ensuring the economic security have been set out. The measures of formation an effective system of economic security that will promote the improvement of the enterprise, stimulation of its economic development, ensuring its increase of profitability and competitiveness in the market have been outlined.
Keywords: state policy; economic security of machine-building enterprises; industry competitiveness; principles of state policy; measures of economic security